The Effect of Different Exposure Times on Some Properties of Three Types Visible Light Cured Acrylic Resins - Abdullqadir Qadir; Rizgar Hasan (Erbil Dental Journal)
Background and Objectives: Visible light cured (VLC) acrylic resin is one of the developed polymeric acrylic resins found to be suitable for many dental applications: Removable, fixed, maxillofacial prostheses. The objective of this study was to evaluate the effect of different exposure times on some mechanical properties of VLC acrylic resins and compare with cold cured acrylic resins.